An influence of workplace victimization on employees’ internet pornography addiction and organizational outcomes - Youngkeun Choi (Taylor & Francis Group, 2019)
The purpose of this study is to investigate if workplace victimization arouses employees’ internet pornography addiction and how it influences their job satisfaction and organizational citizenship behavior. And, this study explores if perceived organizational support can be an organizational factor moderating the relationship between workplace victimization and internet pornography addiction. For this, this study collected data from 305 employees in Korean companies through a survey method. In the results, first, the more employees suffer from workplace victimization, they are more likely to be addictive in internet pornography. Second, the more addictive employees are in internet pornography, their job satisfaction and organizational citizenship behavior decreases. Finally, when employees perceive more support provided by the organization, they are less likely to be addictive in internet pornography which is aroused by workplace victimization.